2017
DOI: 10.1093/ckj/sfx054
|View full text |Cite
|
Sign up to set email alerts
|

Depressive affect in incident hemodialysis patients

Abstract: BackgroundThe prevalence of depressive affect is not well defined in the incident hemodialysis (HD) population. We investigated the prevalence of and associated risk factors and hospitalization rates for depressive affect in incident HD patients.MethodsWe performed a prospective investigation using the Patient Health Questionnaire 2 (PHQ2) depressive affect assessment. From January to July of 2013 at 108 in-center clinics randomly selected across tertiles of baseline quality measures, we contacted 577 and 543 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Depression has been consistently associated with increased mortality risk among patients receiving dialysis [3], but whether depression is associated with cardiovascular/infection events in these patients has not been well explored. Previous studies show inconsistencies in the association of depression with adverse outcomes [5, 1620], often hampered by small sample sizes, outcome ascertainment bias, inadequate adjustment for confounding variables and short-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Depression has been consistently associated with increased mortality risk among patients receiving dialysis [3], but whether depression is associated with cardiovascular/infection events in these patients has not been well explored. Previous studies show inconsistencies in the association of depression with adverse outcomes [5, 1620], often hampered by small sample sizes, outcome ascertainment bias, inadequate adjustment for confounding variables and short-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the KDQOL we also employed the PHQ-2 which is a self-administered questionnaire that is specifically made for assessing depression severity (17), but has been validated for hemodialysis patients (18).…”
Section: Methodsmentioning
confidence: 99%
“…Ravaghi et al [ 3 ] found that the prevalence of depression among MHD patients in Iran was estimated to be 62%, and a South Korean study reported that moderate to severe depression is common in MHD patients and is associated with health-related quality of life [ 4 ]. Depression increases the rate of hospital admissions, the duration of hospitalization, and the risk of death in patients undergoing MHD [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%